EFEKTIVITAS PELAKSANAAN TUGAS PEGAWAI DI DISTRIK KAIMANA KABUPATEN KAIMANA PROVINSI PAPUA BARAT - MUFARA, YAHYA; Tulusan, Femmy; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: the phenomenon of the problem shows the Organization of the work of existing employees inthe District of Kaimana haven't gone well, among others seen in the administrative service is still slowas in the data rendering the poor district of Kaimana in some wards, the coordination of work activities– activities of community empowerment. Based on the issue, then that becomes the goal of the research isto find out the effectiveness of the implementation of the duties of a clerk in the Districtof Kaimana Regency Kaimana of West Papua ProvinceThis research uses qualitative descriptive analysis with design. This design becausethe election as research purposes i.e. describes the effectiveness of the implementation of the duties of aclerk in the District of Kaimana Regency Kaimana of West Papua Province. Theinformant i.e. research people who understood by researchers havedata and information needed in thisresearch to describe the effectiveness of the implementation of the duties of a clerk in the Districtof Kaimana Regency Kaimana of West Papua Province. Then the informants have been interviewed inthis study a total of 10 peopleThe results showed that the effectiveness of the work of employees in the DistrictofKaimana Regency Kaimana of West Papua Province has not been fully achieved wellseen from theaspect of production, efficient use, satisfaction, adaptation and developmentKey words: effectiveness, Performance, Employee